ChemInform Abstract: Total Synthesis of (.+‐.)‐Aspidophylline A. Issue 32 (24th July 2014) - Ren, Weiwu; Wang, Qian; Zhu, Jieping
Abstract The synthesis features a rapid access to a fully functionalized dihydrocarbazole through 1) desymmetrization of readily available 2‐allyl‐2‐(o‐nitrophenyl)cyclohexane‐1, 3‐dione; 2) an intramolecular azidoalkoxylation of an enecarbamate installing both the furoindoline ring and the azido functionality; and 3) an intramolecular Michael addition for the construction of the 2‐azabicyclo[3.3.1]nonane ring system